Comparison and correction of element measurements using XRF core scanning and ICP-AES methods in lacustrine sediments. Issue 6 (March 2020) - Cheng, Aiying; Yu, Junqing; Gao, Chunliang; Zhang, Lisha
Abstract: An integrated analysis has been carried out on core dated by qualitative X-ray fluorescence core scanning combination of quantitative ICP-AES in order to characterize the extent of elements Cd, Cr, Cu, Zn, and Pb in the Lake Toson in the northeastern Tibet Plateau. When combining both the quantitative and qualitative measurements, we observed a significantly positive correlation. Comparing the ratios between element intensities and concentration, we found that the XRF element intensities were related to the amount of water. Using the intensity of Cl as an indicator of water content, the element intensities of Cd, Cr, Cu, Zn, and Pb in the core samples were corrected. The correlation coefficients of each pairs of the two datasets among Cd, Cr, Cu, Zn, and Pb were significantly raised. These data sets with highly correlations were used to produce a transfer function to relate XRF element intensity with element concentration. Calculated element concentrations from the intensities show only minor differences from concentrations obtained by ICP-AES, indicating XRF core scanners are a very useful tool for measuring element concentration in lacustrine sediments.